Analyst Forecasts and the Cost of Capital: Evidence from Indonesian State-Owned Enterprises - Muslimin Muslimin; R. A. Fiska Huzaimah (Peradaban Journal of Economic and Business, 2026)
This study investigates the determinants of the Weighted Average Cost of Capital (WACC) for Indonesian State-Owned Enterprises (SOEs) under the Indonesia Investment Authority (BP Danantara), focusing on the interplay between capital market analyst forecasts and macroeconomic factors. Utilizing a quantitative explanatory design, the research employs logistic regression on a pooled dataset of financial and non-financial SOEs. The findings reveal distinct sectoral variations in WACC drivers. For non-financial SOEs, inflation is the sole significant factor, exerting a negative effect. Conversely, for financial SOEs, the debt-to-assets (DTA) ratio, firm size, and interest rates significantly and negatively influence WACC within a robust model. Notably, analyst forecasts do not yield a direct significant effect for either sector. The study concludes that WACC determinants are fundamentally sector-specific: financial SOEs are more sensitive to monetary policy and capital structure, whereas non-financial SOEs are primarily influenced by real economic conditions. These results suggest that financial SOE managers should prioritize capital structure optimization and interest rate responsiveness, while non-financial SOEs must focus on operational efficiency. Academically, this research affirms that fundamental factors, rather than short-term analyst sentiment, remain the primary drivers of corporate cost of capital in the Indonesian SOE landscape. Penelitian ini bertujuan untuk menganalisis determinan Weighted Average Cost of Capital (WACC) pada Badan Usaha Milik Negara (BUMN) di bawah naungan Badan Pengelola (BP) Danantara sebagai Indonesia Investment Authority. Fokus utama penelitian ini adalah interaksi antara proyeksi analis pasar modal dan faktor-faktor makroekonomi. Dengan menggunakan desain eksplanatori kuantitatif, penelitian ini menerapkan analisis regresi logistik pada data panel BUMN sektor keuangan dan non-keuangan. Temuan penelitian menunjukkan adanya perbedaan sektoral yang signifikan pada determinan WACC. Pada BUMN non-keuangan, hanya inflasi yang menunjukkan pengaruh negatif signifikan. Sebaliknya, pada BUMN keuangan, debt-to-assets (DTA), ukuran perusahaan (firm size), dan tingkat suku bunga berpengaruh negatif secara signifikan dalam model yang kokoh. Sementara itu, proyeksi analis tidak menunjukkan pengaruh langsung yang signifikan pada kedua kelompok tersebut. Penelitian ini menyimpulkan bahwa determinan WACC bersifat spesifik sektoral: BUMN keuangan lebih sensitif terhadap kebijakan moneter dan struktur modal, sedangkan BUMN non-keuangan lebih dipengaruhi oleh kondisi ekonomi riil seperti inflasi. Temuan ini memberikan implikasi praktis bagi manajemen BUMN keuangan untuk memprioritaskan pengelolaan struktur modal dan respons terhadap perubahan suku bunga, sementara BUMN non-keuangan perlu memperkuat efisiensi operasional. Secara akademis, hasil ini menegaskan bahwa faktor fundamental, alih-alih sentimen analis jangka pendek, merupakan penggerak utama biaya modal perusahaan.